Pelatihan Pembelajaran Al-Qur’an dengan Metode Ummi di SD Negeri 2 Glinggang, Sampung, Ponorogo - Al Faruqi, Achmad Reza Hutama; Amrullah, Khasib; Fairuzzabadi, Fairuzzabadi; Ilham, Muhammad; Anwarudin, Aan; Ramadhan, Yusuf Khairul; Dzilhilmi, Ubaid; Al Hakim, Risydan Billy; Hariri, Muhammad Hisyam; Jahidin, Al Mul; Al-Abid, Muhammad Ramdhan (Abdimas Indonesian Journal, 2024)
This article aims to present Quranic learning training using the UMMI method at SDN 002 Glinggang, Sampung, Ponorogo, with a focus on expanding knowledge and facilitating Quranic learning for participants more easily. The problem faced by the participants is the lack of clear methods in learning the Quran. To address this challenge, the Community Service Program (Kuliah Kerja Nyata/KKN) team from UNIDA Gontor organized training and education on Quranic learning methods for students and teachers. This community service method includes stages of preparation, implementation, monitoring, and evaluation. It is hoped that the learning and training activities using the UMMI method can become a method that is consistently used in teaching the Quran to all students of SDN 002 Glinggang, Sampung, Ponorogo, and improve the accuracy of their Quranic readings. The results of this community service are evident in the improvement of Quranic reading quality among students at SDN 002 Glinggang, Sampung, Ponorogo.